Police Authority Regarding Modification of Motorized Vehicles That Are Not Roadworthy Standards - I Putu Edi Rusmana (Magister of Law, Post Graduate Program, Universitas Warmadewa, 2024)
This research discusses about the authority of the Indonesian National Police regarding law enforcement in modifying motorized vehicles that are roadworthy on road. The problem of this research is how is law enforcement enforced against perpetrators who modify motorized vehicles? and what are the criminal sanctions against motorists who modify vehicles that are not roadworthy? The purpose of this research is to find out the authority of the police in enforcing the law and criminal sanctions related to modifying motor vehicles that are unfit for the road. In this research used a normative legal research method, namely by reviewing or analyzing several legal materials from several literatures and statutory regulations that are related. It is hoped that the research carried out by researchers will provide theoretical and practical benefits. Theoretical usefulness means that the results of this research are useful for developing knowledge and the practical usefulness of this research means that it has good benefits for the government, related institutions or society at large. The results of this research are that the police enforcing traffic laws, especially modifying vehicles that do not pass the roadworthy test, are in line with government regulations and the role of the Indonesian National Police in carrying out their duties and obligations to curb traffic violations is in accordance with legislation in Law Number 22 of 2009 on Road Traffic and Transportation. Criminal sanctions in traffic have been regulated in Law Number 22 of 2009 on Road Traffic and Transportation.